A combined control approach for industrial process systems using feed-forward and adaptive action based on second order sliding mode controller design. (February 2019) - Dumlu, Ahmet; Ayten, Kağan Koray
This paper presents a new method that uses a feed-forward adaptive second order sliding mode control (FF-ASSMC) for a coupled tank process system that is often used in industry. This proposed method is to combine a feedforward action with adaptive feedback for robust performance of the couple tank system for the first time. The reason for using this feedforward action with the feedback sliding mode control (SMC) is to reduce the effect of the measured disturbance on the coupled tank system. In addition to this, an adaptive second-order SMC proposes to track the desired tank's level trajectories under disturbances and uncertainties. In order to illustrate the efficiency of the proposed FF-ASSMC method, the simulation and real time experimental studies have been realized. The simulation and experimental outcomes strongly verified that the proposed controller gives a quite successful trajectory tracking response and smaller magnitude overshot under external disturbances.